Collaborative Governance in the Implementation of Sewing Training Program - Nur Afifah; Sungkowo Edy Mulyono (Jurnal Pemberdayaan Masyarakat, 2025)
The government continues to strive to reduce the unemployment rate through competency-based training programs at the Job Training Center. This study aims to investigate the implementation of collaborative governance in the sewing training program at UPTD BLK Kendal, employing a qualitative approach and a case study research design. Data were obtained through interviews, observations, and documentation, and then analyzed interactively using Ansell Gash's theory. The results showed that the collaboration process went quite well through five stages: (1) Face to face dialogue through FKLPID; (2) BLK trust building gives full trust to LPK as the technical implementer of training; (3) Commitment to process through MoU; (4) Share to understanding already has the same understanding of the output and outcomes of the training program; and (5) Intermediate outcomes of the success of trainees in the competency test and absorbed into the world of work. As well as intermediate results in the form of certified graduates and absorbed work. However, there are still challenges such as suboptimal communication, participant readiness, and differences in training facilities. This research is expected to contribute to enhancing the effectiveness and efficiency of training program implementation strategies and strengthening collaboration among stakeholders to address unemployment.